Development of Snack Recipes Using Sucralose Instead of Sugar - Rueangsri, Narisa; Booranasuksakul, Uraiporn; Singhato, Alongkote (Journal of Nutrition Association of Thailand (Online), 2018)
Non-communicable diseases are one of the most deleterious health conditions commonly found in communities caused from long-term high amount of sugar intake. This study aimed to develop the satisfied snacks recipes using the sucralose as sweetener. Forty of participants who met the inclusion and exclusion criteria were recruited to conduct the sensory evaluation at the Faculty of Allied Health Sciences, Burapha University, Bang Saen campus, to determine their satisfaction on appearance, color, texture, flavor, taste, and overall satisfaction toward the developed snacks using the 5 level-hedonic scale. The most5 selected snacks(mixed fruits custard, aclair, pancake, strawberry pudding, and pineapple pie) were developed into sugar formula and sucralose formula. In general, results revealed there were no significant differences in all aspects of the 5 developed snacks, except for pancake which the average score on texture of sucralose formula was significantly higher than sugar formula (p<0.05) and strawberry pudding which the average score on color of sugar formula was significantly higher than sucralose formula (p<0.05). In addition, the average overall satisfaction scores indicated that participants were satisfied with all developed snacks using sucralose as sweetener. In conclusion, the developed snacks using sucralose as sweetener were satisfied and acceptable from participants.